How Did Orthopaedic Surgeons Perform in the 2018 Centers for Medicaid & Medicare Services Merit-based Incentive Payment System?. Issue 1 (January 2022) - Cwalina, Thomas B.; Jella, Tarun K.; Acuña, Alexander J.; Samuel, Linsen T.; Kamath, Atul F.
Abstract: Background: The Merit-based Incentive Payment System (MIPS) is the latest value-based payment program implemented by the Centers for Medicare & Medicaid Services. As performance-based bonuses and penalties continue to rise in magnitude, it is essential to evaluate this program's ability to achieve its core objectives of quality improvement, cost reduction, and competition around clinically meaningful outcomes. Questions/purposes: We asked the following: (1) How do orthopaedic surgeons differ on the MIPS compared with surgeons in other specialties, both in terms of the MIPS scores and bonuses that derive from them? (2) What features of surgeons and practices are associated with receiving penalties based on the MIPS? (3) What features of surgeons and practices are associated with receiving a perfect score of 100 based on the MIPS? Methods: Scores from the 2018 MIPS reporting period were linked to physician demographic and practice-based information using the Medicare Part B Provider Utilization and Payment File, the National Plan and Provider Enumeration System Data (NPPES), and National Physician Compare Database. For all orthopaedic surgeons identified within the Physician Compare Database, there were 15, 210 MIPS scores identified, representing a 72% (15, 210 of 21, 124) participation rate in the 2018 MIPS. Those participating in the MIPS receive a final score (0 to 100, with 100 being a perfect score) based on a weighted calculation of performance metrics across four domains: quality, promoting interoperability, improvement activities, and costs. In 2018, orthopaedic surgeons had an overall mean ± SD score of 87 ± 21. From these scores, payment adjustments are determined in the following manner: scores less than 15 received a maximum penalty adjustment of -5% ("penalty"), scores equal to 15 did not receive an adjustment ("neutral"), scores between 15 and 70 received a positive adjustment ("positive"), and scores above 70 (maximum 100) received both a positive adjustment and an additional exceptional performance adjustment with a maximum adjustment of +5% ("bonus"). Adjustments among orthopaedic surgeons were compared across various demographic and practice characteristics. Both the mean MIPS score and the resulting payment adjustments were compared with a group of surgeons in other subspecialties. Finally, multivariable logistic regression models were generated to identify which variables were associated with increased odds of receiving a penalty as well as a perfect score of 100. Results: Compared with surgeons in other specialties, orthopaedic surgeons' mean MIPS score was 4.8 (95% CI 4.3 to 5.2; p < 0.001) points lower. From this difference, a lower proportion of orthopaedic surgeons received bonuses (-5.0% [95% CI -5.6 to -4.3]; p < 0.001), and a greater proportion received penalties (+0.5% [95% CI 0.2 to 0.8]; p < 0.001) and positive adjustments (+4.6% [95% CI 6.1 to 10.7]; p < 0.001) compared with surgeons in other specialties. After controlling for potentially confounding variables such as gender, years in practice, and practice setting, small (1 to 49 members) group size (adjusted odds ratio 22.2 [95% CI 8.17 to 60.3]; p < 0.001) and higher Hierarchical Condition Category (HCC) scores (aOR 2.32 [95% CI 1.35 to 4.01]; p = 0.002) were associated with increased odds of a penalty. Also, after controlling for potential confounding, we found that reporting through an alternative payment model (aOR 28.7 [95% CI 24.0 to 34.3]; p < 0.001) was associated with increased odds of a perfect score, whereas small practice size (1 to 49 members) (aOR 0.35 [95% CI 0.31 to 0.39]; p < 0.001), a high patient volume (greater than 500 Medicare patients) (aOR 0.82 [95% CI 0.70 to 0.95]; p = 0.01), and higher HCC score (aOR 0.79 [95% Cl 0.66 to 0.93]; p = 0.006) were associated with decreased odds of a perfect MIPS score. Conclusion: Collectively, orthopaedic surgeons performed well in the second year of the MIPS, with 87% earning bonus payments. Among participating orthopaedic surgeons, individual reporting affiliation, small practice size, and more medically complex patient populations were associated with higher odds of receiving penalties and lower odds of earning a perfect score. Based on these findings, we recommend that individuals and orthopaedic surgeons in small group practices strive to forge partnerships with larger hospital practices with adequate ancillary staff to support quality reporting initiatives. Such partnerships may help relieve surgeons of growing administrative obligations and allow for maintained focus on direct patient care activities. Policymakers should aim to produce a shortened panel of performance measures to ensure more standardized comparison and less time and energy diverted from established clinical workflows. The current MIPS scoring methodology should also be amended with a complexity modifier to ensure fair evaluation of surgeons practicing in the safety net setting, or those treating patients with a high comorbidity burden. Level of Evidence: Level III, therapeutic study.